Comparison of Pain Perception in Patients Affected by Cleft and Cranio Facial Anomalies Treated With Traditional Fixed Appliances or Invisalign. (January 2020) - Meazzini, Maria Costanza; Tortora, Chiara; Mazzoleni, Fabio; Autelitano, Luca
Introduction: The objective of this prospective study was to compare the difference in pain perception between treatment with aligners (AL) and fixed appliances (FA) in patients affected by cleft and craniofacial anomalies (CFA). Methods: The sample consisted of 100 syndromic caucasian patients affected by various CFA from 2 different hospitals. Fifty patients treated with AL were matched for sex, age, and CFA with a control sample of 50 patients treated with FA. A modification of the Mc Gill Pain Questionnaire was adapted to our needs. Results: Statistical differences were found. Aligners induced more tightness and tension than FA, while FA induced more pain descriptors and patients reported a higher intake of painkillers. Conclusions: The results of this study documented a higher pain perception with FA than with AL in patients affected by CFA. The higher sensitivity to pain in cleft and craniofacial patients with fixed treatment could be related to their higher prior sensitization, given the past surgeries and orthodontic treatments. Thus, this study might suggest that Invisalign treatment might be a further interesting treatment option for patients with cleft in order to reduce their burden of orthodontic pain.